Empowering Urban Farmers: An Asynchronous Learning Application for Greenhouse Management - Wibowo, Mars Caroline; Santoso, Joseph Teguh (Journal of Technology Informatics and Engineering, 2024)
This paper addresses the growing need for effective educational tools in greenhouse gardening, particularly for beginners lacking prior agricultural knowledge. Despite the increasing availability of mobile applications aimed at agricultural education, many existing resources fail to engage users through interactive experiences, thereby limiting their practical skill development. This study identifies a significant knowledge gap regarding the specific needs of novice gardeners and the effectiveness of current educational applications. To address this gap, we developed an innovative mobile application designed to facilitate asynchronous learning through interactive features such as discussion forums and quizzes. A mixed-methods approach was employed, involving user testing with 30 participants to evaluate the application’s usability and engagement levels. The results indicated that 90% of users found the application intuitive and easy to navigate, with enhanced motivation attributed to its engaging visual design. These findings suggest that the proposed application not only meets the educational needs of users but also fosters a more interactive and responsive learning environment. The implications of this research highlight the potential for mobile applications to significantly improve practical knowledge and skills in greenhouse management, ultimately contributing to more sustainable agricultural practices